IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA BADAN USAHA MILIK DAERAH (STUDI PADA PERUSAHAAN AIR MINUM (PAM) PROVINSI JAKARTA) - Sari, Klara Kumala; Sriyono, Muhammad Edo Edi; Mawarni, Linda; Katu, Florence Yacoba (JOURNAL AKSES STIA MALANG, 2025)
As an institution under local government supervision, Regional-Owned Enterprises (BUMD) carry a significant mandate to provide public services and optimize regional assets through the implementation of good corporate governance (GCG). In their operations, BUMDs need to achieve optimal management by prioritizing efficiency, accountability, and transparency in managing various local government resources. The successful implementation of GCG in BUMDs depends on the application of five core principles: transparency,accountability, fairness, independence, and social and environmental responsibility. The application of these mprinciples is directed toward establishing a transparent management system and minimizing opportunities for misconduct and abuse of power. This study aims to examine the implementation of good corporate governance in the context of BUMDs. The approach used in data processing employs qualitative research methods with an emphasis on secondary data collection. The study's findings reveal that throughout 2023, PAM Jaya has implemented regional enterprise management in accordance with good corporate governance principles, as reflected in the achievement of best practice values in each aspect of its principles.